Inovasi Produk, Kemasan dan Pemasaran untuk Meningkatkan Pendapatan UMKM Kelurahan Kariajawa Dompu - Nafisah Nurulrahmatiah; Zahra Sausan; Jumiyati Jumiyati (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this community service is to provide assistance to MSMEs producing traditional cakes and tampah craftsmen in Karijawa Village, Dompu District, Dompu Regency. The assistance provided includes flavor innovations in traditional Dompu cakes and innovations in bamboo crafts other than tampah. These innovations aim to increase the competitiveness of local products in the wider market. This assistance also focuses on improving the quality of product packaging, considering that the still minimal packaging quality is one of the obstacles faced by partners. As part of this community service, we hope to provide solutions to the problems faced by MSME partners related to unattractive products and less than optimal packaging quality. The method used in this activity includes three main stages: planning, implementation, and evaluation. The planning stage is carried out by identifying the problems faced by partners and selecting appropriate solutions. In the implementation stage, the selected solutions are implemented by providing training and direct assistance related to flavor innovations in traditional biruas beras cakes and bamboo woven product designs. The evaluation stage aims to assess the extent to which the implemented solutions have been effective and have a positive impact on MSME partners. The results of this community service activity indicate that MSME partners now have products with new flavors for their rice bran and a wider variety of woven bamboo products, in addition to winnowing baskets. Furthermore, product packaging has undergone significant improvements, increasing product appeal and meeting higher market standards.